KONSEP PAULUS MENGENAI PERNIKAHAN - Manase Gulo (Manna Rafflesia, 2016)
This paper wants to explain Paul's understanding of marriage. In this paper I will write down the problems that the Apostle Paul saw in the married life of the church he served, including the occurrence of insecs and perversions of understanding of the body and freedom. These deviations have been criticized by the Apostle Paul. Therefore in the next section will write how a husband and wife relationship should be in a marriage.